Incidence of Associated Injuries in Patients with ACL Tear on MRI – An Observational Study - Dr. Varun S.; Dr. Bukke Ravindra Naik; Dr. V. Suresh Kumar; Dr. Sahana S. (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background Anterior cruciate ligament (ACL) injuries are common, particularly in athletes, and often occur with additional knee injuries, including meniscal tears, ligamentous damage, and bone bruises. Identifying the incidence of these associated injuries is critical for optimizing treatment and improving recovery outcomes. Objectives This study aims to determine the incidence of associated injuries in patients with ACL tears and to explore the demographic profile and injury mechanisms that contribute to these additional knee injuries. Methods A multicentre, prospective observational study was conducted from December 2023 to December 2024, involving 200 patients diagnosed with ACL tears confirmed via MRI. Associated injuries such as meniscal tears, collateral ligament injuries, cartilage damage, and bone bruises were documented. Data on injury mechanisms, demographics, and sports participation were collected. Results Out of the 200 patients, 50% (n=100) had at least one associated injury. Meniscal tears were the most common (42%), followed by bone bruises (22%) and MCL injuries (18%). The majority of ACL injuries were due to non-contact mechanisms (60%), with football and basketball being the most frequent sports. Conclusion ACL tears frequently occur with associated knee injuries, particularly meniscal and ligamentous damage. These findings highlight the need for comprehensive diagnostic and treatment strategies to address multiple injuries and improve rehabilitation outcomes.